ORGANIZATION AND CONDUCT OF LABORATORY WORK IN TEACHING THE METHODOLOGY OF SOCIOLOGICAL RESEARCH (ResearchJet Journal of Analysis and Inventions, 2022)
This article provides information on the methods of organizing and conducting laboratory training as a methodical recommendation for the practical application of the theoretical knowledge obtained for the formation of knowledge, skills and skills of students in the field of methodology of sociological research .